Maternal exposure to hydroxychloroquine and birth defects. Issue 17 (23rd July 2021) - Howley, Meredith M.; Werler, Martha M; Fisher, Sarah C; Van Zutphen, Alissa R; Carmichael, Suzan L; Broussard, Cheryl S; Heinke, Dominique; Ailes, Elizabeth C; Pruitt, Shannon M; Reefhuis, Jennita; Mitchell, Allen A.; Browne, Marilyn L.; et al.
Abstract: Background: Hydroxychloroquine is a treatment for rheumatic disease and considered safe during pregnancy. Interest in hydroxychloroquine has increased as it is being examined as a potential treatment and prophylaxis for coronavirus disease 2019. Data on the risks of specific birth defects associated with hydroxychloroquine use are sparse. Methods: Using data from two case–control studies (National Birth Defects Prevention Study and Slone Epidemiology Center Birth Defects Study), we described women who reported hydroxychloroquine use in pregnancy and the presence of specific major birth defects in their offspring. Cases had at least one major birth defect and controls were live‐born healthy infants. Women self‐reported medication use information in the few months before pregnancy through delivery. Results: In total, 0.06% (19/31, 468) of case and 0.04% (5/11, 614) of control mothers in National Birth Defects Prevention Study, and 0.04% (11/29, 838) of case and 0.05% (7/12, 868) of control mothers in Birth Defects Study reported hydroxychloroquine use. Hydroxychloroquine users had complicated medical histories and frequent medication use for a variety of conditions. The observed birth defects among women taking hydroxychloroquine were varied and included nine oral cleft cases; the elevated observed:expected ratios for specific oral cleft phenotypes and for oral clefts overall had 95% confidence intervals that included 1.0. Conclusion: While teratogens typically produce a specific pattern of birth defects, the observed birth defects among the hydroxychloroquine‐exposed women did not present a clear pattern, suggesting no meaningful evidence for the risk of specific birth defects. The number of exposed cases is small; results should be interpreted cautiously.